Strategic planning in a turbulent environment: evidence from the oil majors - Grant, Robert M. (Strategic Management Journal, 2003)
Abstract The long‐running debate between the ‘rational design’ and ‘emergent process’ schools of strategy formation has involved caricatures of firms' strategic planning processes, but little empirical evidence of whether and how companies plan. Despite the presumption that environmental turbulence renders conventional strategic planning all but impossible, the evidence from the corporate sector suggests that reports of the demise of strategic planning are greatly exaggerated. The goal of this paper is to fill this empirical gap by describing the characteristics of the strategic planning systems of multinational, multibusiness companies faced with volatile, unpredictable business environments. In‐depth case studies of the planning systems of eight of the world's largest oil companies identified fundamental changes in the nature and role of strategic planning since the end of the 1970s. The findings point to a possible reconciliation of ‘design’ and ‘process’ approaches to strategy formulation. The study pointed to a process of planned emergence in which strategic planning systems provided a mechanism for coordinating decentralized strategy formulation within a structure of demanding performance targets and clear corporate guidelines. The study shows that these planning systems fostered adaptation and responsiveness, but showed limited innovation and analytical sophistication. Copyright © 2003 John Wiley & Sons, Ltd.